(3GdRghQ GdeTQbI hGdfaMGJ GdYHbIs - (3jhSa Hf CMeO Hf eMeO Hf YKeGfs ((3OGhO Hf jhSa Hf UGdM s)
(3ChdgG (B:s
(3jHOC HcJGH GdTaYI Hbhdg (B: (3dgG eYfjGf dZg hEUWdGMkG , CeG ai GddZI agi s
(3BNQgG (B:s
(3hJMUd HYO gPG GdJMUjd ddCejQ QMeg Gddg JYGdi Je GdSaQ GdKGfi s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfGhjjf HGdMeQIs
(3hYdi MhGTjgG HYV GdJYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdESdGejs